Optimality Condition and Distributed Optimization for Economic Dispatch Using a Novel Weighted Incremental Cost Consensus Approach - Alvi, Um-E-Habiba; Ahmed, Waqas; Hong, Keum-Shik; Rehan, Muhammad; Ahmed, Shakeel (Frontiers in Energy Research, 2022)
This research report investigates a novel optimization approach for the economic dispatch problem (EDP) problem based on the weighted sum of generators’ costs under supply-demand balance. Unlike conventional approaches, we present a distributed optimization approach that ensures optimality using weighted incremental cost (IC) consensus and sign-consensus error convergence. We can apply the optimization of a weighted sum of generators’ costs to address several constraints, like capacity and environmental constraints, in addition to the supply-demand balance. The proposed distributed weighted IC consensus approach has been applied to the IEEE-30 bus and IEEE-118 bus systems over a communication topology. The results indicate the efficacy of weights to address generation constraints and the convergence of weighted ICs under supply-demand balance.